Liquidity and the convergence to market efficiency. Issue 3 (3rd July 2018) - Young, Nicara; Auret, Christo
ABSTRACT: The aim of this study is to investigate the relationship between market liquidity changes on the Johannesburg Stock Exchange (JSE) and the market's degree of efficiency. Market efficiency is characterised in terms of two philosophies: Fama's (1970) Efficient Markets Hypothesis (EMH), and Shiller's (1981; 2003) informational efficiency designation. Efficiency was tested using measures of return predictability, a random walk benchmark and price volatility; liquidity was measured using market turnover. The tests were conducted on JSE Top 40 shares across three regimes, spanning January 2012–June 2016. The regimes are demarcated by two structural breaks in the JSE's microstructure: the 2012 trading platform upgrade and the 2014 colocation centre launch. The results show that past order imbalances are a significant predictor of daily returns, although the significance of this predictability has dissipated over time. Return predictability is not influenced by liquidity. In fact, there is evidence that illiquidity weakens return predictability. Prices were closer to random walk benchmarks during the third regime. In consideration of informational efficiency, during the latter two regimes price volatility is greater during trading versus non-trading hours. This is coupled with an emergence of nonlinear return dependence, which is indicative of greater mispricing. Thus, over the three regimes, market efficiency improved in the sense of the EMH, but informational efficiency deteriorated. This study contributes to the field by: introducing an inverse measure of market efficiency; providing insight into the measure's time variation and relation to liquidity; and demonstrating that market efficiency tests should incorporate the dual meanings of the term, enabling richer understanding of how such meanings intersect.